Effect of dynamical screening on quantized longitudinal electrical conductivity in neutron star mergers. (1st October 2022) - Sarkar, S; Adhya, S P
Abstract: We present the calculation of longitudinal electrical conductivity in magnetized plasma considering dynamical screening in the context of binary neutron star mergers. We consider strongly quantizing domain for significant modification in the transport coefficient due to magnetic field. Boltzmann equation is solved to obtain dissipative component of the electrical conductivity tensor in presence of magnetic field. The longitudinal electrical conductivity is formulated considering dynamically screened medium with magnetically modified screening. Numerical evaluations show that the effect of screening on electrical conductivity is less whereas inclusion of dynamical screening results in profound modification. Dynamical screening reduces electrical conductivity leading to a reduction in relevant magnetic field decay time scale.